Adherence and healthcare utilization among older adults with COPD and depression. (August 2017) - Albrecht, Jennifer S.; Khokhar, Bilal; Huang, Ting-Ying; Wei, Yu-Jung; Harris, Ilene; Moyo, Patience; Hur, Peter; Lehmann, Susan W.; Netzer, Giora; Simoni-Wastila, Linda
Abstract: Background and objective: Adherence to chronic obstructive pulmonary disease (COPD) maintenance medications and antidepressants may reduce healthcare utilization among multimorbid individuals with COPD and depression. We quantified the independent effects of adherence to antidepressants and COPD maintenance medications on healthcare utilization among individuals co-diagnosed with COPD and depression. Procedures: We conducted a retrospective cohort study using a 2006–2012 5% random sample of Medicare beneficiaries co-diagnosed with COPD and depression who had two or more prescription fills of both COPD maintenance medications and antidepressants. We measured adherence to medications using the proportion of days covered per 30-day period. The primary outcomes were all-cause emergency department (ED) visits and hospitalizations. Beneficiaries were followed over a minimum 12-month follow-up period. Results: Of the 16, 075 beneficiaries meeting inclusion criteria, 21% achieved adherence ≥80% to COPD maintenance medications and 55% achieved adherence ≥80% to antidepressants. Compared to no use and controlling for antidepressant adherence and potential confounders, higher (≥80%) levels of adherence to COPD maintenance medications were associated with decreased risk of ED visits (hazard ratio (HR) 0.79; 95% CI 0.74, 0.83) and hospitalizations (HR 0.82; 95% CI 0.78, 0.87). Similarly, higher levels (≥80%) of adherence to antidepressants resulted in decreased risk of ED visits (HR 0.74; 95% CI 0.70, 0.78) and hospitalizations (HR 0.77; 95% CI 0.73, 0.81) compared to no use. Conclusions: Clinicians can assist in the improved management of their multimorbid patients' health by treating depression among patients with COPD and monitoring and encouraging adherence to the regimens they prescribe. Highlights: 1 in 5 older adults with COPD and depression achieve adherence of 80% or greater to COPD maintenance medications. Antidepressant adherence was greater, with 1 in 2 older adults achieving adherence levels of 80% or better. Higher adherence with both medications was associated with lower risk of emergency department visits and hospitalizations. Understanding COPD and depression regimens may prevent unavoidable adverse events among depressed older adults with COPD.